Small signal stability and dynamic performance investigation on multi-machines power system including DFIG wind farm - Khaled Kouider; Abdelkader Bekri (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The boundless potential of wind power in augmenting global energy production is a promising prospect. The efficient design and cost-effectiveness of doubly fed induction generator (DFIG) wind systems make them an optimistic solution for incorporating wind power on a massive scale. However, integrating these systems into power grids poses several challenges, including power system stability. This study examines the small signal stability and dynamic performance of a modified Western System Coordinating Council (WSCC) 9-bus system including a DFIG wind farm using load flow analysis, and both electromechanical oscillations and eigenvalue analysis. Three case studies were conducted based on the DFIG location and power increment.The simulation is carried out with the aid of the power system analysis toolbox (PSAT) that operates within the MATLAB environment. The study’s findings suggest that the perturbation and location of the DFIG relative to the system’s load have a minimal influence on the overall system’s stability and efficiency. However, when considering damping ratio, power angle, and rotor speed deviations, generators 1 and 2 with the perturbed DFIG installed on bus 8 are the most sensitive units to instability. Hence, larger perturbations and different DFIG’s location influence on power systems necessitates further analysis.